Marketing Mix Factors Affecting Consumer Online Shopping Decisions In Narathiwat Province After the COVID-19 Situation - Grodgangunt, Sumalee; Satabodee, Chonlakan; Tongintharach, Mathurose; Padungrat, Rungsiri (Journal of Management Science Nakhon Pathom Rajabhat University, 2024)
The objectives of this research are 1) to study and compare consumers’ online purchasing decisions. in Narathiwat province After the COVID-19 situation classified by personal factors 2) To study marketing mix factors that affect consumers’ online purchasing decisions. in Narathiwat province after the COVID-19 situation, quantitative research methods the sample group is consumers who purchase products online in Narathiwat Province. there were 400 people. Data were collected using questionnaires. Statistics used in the research include frequency, percentage, mean, standard deviation, t-test, F-test, and multiple regression analysis using a stepwise method. The results of the research found that 1) Comparative analysis of consumers’ online purchasing decisions. in Narathiwat province After the COVID-19 situation, it was found that consumers with different genders, ages, and educational levels and monthly income are different. Consumers decide to buy products online. in Narathiwat province After the COVID-19 situation Not different 2) Marketing mix factors have a positive effect on consumers’ online purchasing decisions. in Narathiwat province After the COVID-19 situation Statistically significant at the .05 level, the marketing mix factor has a predictive power of 75.30 percent. Article history: Received 5 July 2023 Revised 26 December 2023 Accepted 27 December 2023 SIMILARITY INDEX = 18.21 %